Internalisasi Nilai-nilai Keislaman Melalui Pendidikan Karakter Berbasis Kewirausahaan - Sofwan Hadikusuma (Islamic University of Indonesia, 2019)
This article describes the implementation of entrepreneurial activities as an approach to the character education. This was a field research wich the data collected through interviews, field observations, and documentation. The research subject is SMPIT Al-Kautsaar Yogyakarta and the object is its entrepreneurial activities. This research found that SMPIT Al-Khairaat Yogyakarta formulated seven entrepreneurial characters as achievement of students' target characters, namely: 1) creative & innovative, 2) honest, 3) abstinence from fighting and hard work, 4) cooperation and togetherness, 5) meticulous , 6) responsibility, and 7) struggle. The seven characters were instilled through the methods of awareness, habituation, and discipline. Those entrepreneurial activities were meant to internalizing Islamic values in students. The internalization is carried out through steps of transformation, transactions, and trans-internalization. As the result, the entrepreneurial activities sucsesfully managed to instill a sincere attitude, willing to share, and honest in students.